Duckat - Gordon, Gaelyn, 1939-; Gaskin, Chris (New York : Scholastic, 1992)
Mabel makes friends with a very odd duck who thinks he's a cat.
1.9
K-3
K-3
School Library Journal
Horn Book Starred
Publisher's Weekly
Keywords: Ducks -- Fiction; Cats -- Fiction; Ducks -- Fiction; Cats -- Fiction